A topological property of β(N) - Anastase Nakassis (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove that the Stone-Cech-compactification of the natural numbers does not admit a countable infinite decomposition into subsets homeomorphic to each other and to the said compactification.